Methotrexate for refractory adult atopic dermatitis leads to alterations in cutaneous IL-31 and IL-31RA expression - Luciana Paula Samorano; Kelly Cristina Gomes Manfrere; Naiura Vieira Pereira; Roberto Takaoka; Neusa Yuriko Sakai Valente; Mirian Nacagami Sotto; Luiz Fernando Ferraz Silva; Maria Notomi Sato; Valeria Aoki (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background: Methotrexate (MTX) is an alternative treatment for patients with moderate/severe atopic dermatitis (AD). Objective: The authors evaluated the effect of MTX on the cutaneous expression of cytokines and chemokines that are involved in the inflammatory response in adult AD patients who received treatment with methotrexate for 24 weeks. Methods: The authors conducted a prospective single-institution cohort study with 12 adults with moderate/severe AD who received oral MTX (15 mg/wk for 24 wks) and 10 non-atopic matched controls. The comparison was made of skin biopsies of lesional and non-lesional skin, pre- and post MTX treatment. The authors analyzed mean epidermal thickness and expression of IL-31, IL-31RA, OSMR, TSLP, Ki67, IL-4 mRNA, IL-6, IL-10, TNF-α, IFN-γ, TARC, and CCL-22. Results: There was a reduction in mean epidermal thickness (p = 0.021), an increase in IL-31RA expression (immunohistochemistry) in the epidermis (p = 0.016) and a decrease in IL-31 gene expression (p = 0.019) on lesional AD skin post-MTX treatment. No significant changes in the cutaneous expression of the other evaluated markers were identified. Study limitations: Small sample size and limited length of follow-up. Conclusions: Treatment with MTX in adults with moderate/severe AD reduced epidermal hyperplasia and changed the cutaneous expression of inflammatory cytokines and receptors that are mainly related to pruritus, including IL-31 and IL-31RA.